THE UNFULFILLED LOVE AND BELONGING NEEDS FOUND BY THE MAIN CHARACTER IN “ANNA KARENINA” BY LEO TOLSTOY: PSYCHOLOGICAL APPROACH - Sianipar, Almita Rumiris; Jusmaya, Ance (SCIENTIA JOURNAL, 2019)
The purpose of this research is to figure out what are causes and effects of unfulfilled love and belonging needs through intimacy in a couple in the main character in Anna Karenina by Leo Tolstoy (1877). In this research, researcher used the theory of Abraham H. Maslow (1970), the Hierarchy of Needs. This research is descriptive qualitative research, In the process of collecting data, researcher used the documentation method by reading the novel "Anna Karenina" and looking for the quotes that related to the formulation of the problem. In the process of analyzing data, researcher used the qualitative method by doing deeper reading technique. The finding of this research are: First, the causes of unfulfilled love and belonging needs towards Anna Karenina's character are getting married without love and affection, age difference, many lies and deception in the family, and Karenin's work and reputation. Second the effects of unfulfilled love and belonging needs in Anna Karenina's character are Anna’s affair with another man, Vronsky, driven away from home, hopeless and depressed, losing her good name, almost divorced, Anna was pregnant from Vronsky, and committing suicide. Thus, it can be concluded that the love and belonging needs towards Anna is unfulfilled.